Hubungan Kecerdasan Emosional dengan Kinerja Guru Pendidikan Kewarganegaraan - Lonto, Apeles Lexi; Umbase, Ruth Sriana; Sanjaya, Dewa Bagus; Wua, Telly D. (Academy of Education Journal, 2024)
This research aims to analyze the relationship between Emotional Intelligence and Teacher Performance. The method used is the Survey Method. The research results show a positive and significant relationship of 0.89 between Emotional Intelligence and the Performance of Civics Teachers in Bitung City. Emotional intelligence includes awareness of self-control, a high sense of empathy, and harmonization in social relationships; where these factors have caused teacher performance in managing and mastering learning, student guidance, and fun and innovative interactive abilities to increase. The implication is that both emotional intelligence and teacher performance can be improved through increasing knowledge and habituation and continuous training in schools with the spirit of being a learning and driving organization.